The EU Common Security and Defence Policy - Koutrakos, Panos (Oxford : Oxford University Press, 2013)
Presenting an analytical overview of the legal foundations of the EU's Common Security and Defence Policy, this book provides a detailed examination of the legal framework and problems faced by the EU's security policy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: European Security and Defense Policy; National security -- Europe; Europe -- Defenses; European Union countries -- Foreign relations